The work of Anthropology in everyday life (Revista LIDER, 2021)
This text centres on the reconceptualization of anthropological activity viewed from the perspective of daily life, an effort that has required the explicitation of the principal areas or spheres of involvement, socially determined, and that exert control from personal individuality, as a clarifying component considered in a selected bibliography. In this case, we expose as point of discussion the incidence of subjectivity as a general factor that, being closed, at the same time can be lead to the investigator and/or reflect from a comprehensive design. The significance visualized through this exercise concerns the social responsibility ascribed to exercising our role in its diverse nuances. To these we add the learning derived from the experiences and oriented toward searching for new objects of knowledge, realizing that we will obtain a relative balance.